2004
DOI: 10.1124/jpet.103.063099
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclooxygenase-2 by Celecoxib Reverses Tumor-Induced Wasting

Abstract: There have been a number of reports suggesting inhibition of prostaglandin production may impact tumor-mediated wasting and levels of associated humoral factors such as hypercalcemia. These reductions were achieved using traditional nonsteroidal anti-inflammatory drugs (NSAIDs), which are often contraindicated in cancer patients. This is especially true during chemotherapeutic regimens due to concerns of bleeding from gastrointestinal and hematopoietic toxicities associated with inhibition of the housekeeping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 30 publications
2
56
0
Order By: Relevance
“…Anecdotally, the use of α-3 omega fatty acids (eicosapentaenoic acid) [52] and thalidomide (potent anti-TNF activity) have been reported [48]. Experimentally, glucocorticoids, aspirin [63], indomethacin [35,79], methotrexate [60], and celecoxib [23], all have been shown to have some efficacy, which are believed to be effective, in part, due to their ability to inhibit NF-ĸB activity [10,32,73,78]. However, these agents are neither potent nor selective for the NF-ĸB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, the use of α-3 omega fatty acids (eicosapentaenoic acid) [52] and thalidomide (potent anti-TNF activity) have been reported [48]. Experimentally, glucocorticoids, aspirin [63], indomethacin [35,79], methotrexate [60], and celecoxib [23], all have been shown to have some efficacy, which are believed to be effective, in part, due to their ability to inhibit NF-ĸB activity [10,32,73,78]. However, these agents are neither potent nor selective for the NF-ĸB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cytokines, the increased activity of COX can be responsible for muscle wasting and cachexia. Activation of COX-2 pathways has been observed in several cachetic state conditions such as cancer and sepsis (15,19). COX inhibitors are able to ameliorate cancer cachexia and to improve body composition both in experimental animals and humans (15,27,39).…”
mentioning
confidence: 99%
“…The celecoxib antitumor effect is well established [44][45][46][47][48][49]. It was shown that treatment with celecoxib reduces Walker-256 tumor growth by mechanisms independent of inhibition in the COX-2/ PGE2 pathway, which involve reduction in the expression of Bcl-xl anti-apoptotic protein, that is, by specific pro-apoptotic actions [19].…”
Section: Discussionmentioning
confidence: 99%